Inhibitory effects of Lentinus edodes mycelia polysaccharide on α-glucosidase, glycation activity and high glucose-induced cell damage. (15th October 2020) - Cao, Xiangyu; Xia, Ying; Liu, Dan; He, Yonglin; Mu, Teng; Huo, Yapeng; Liu, Jianli
Graphical abstract: Lentinus edodes mycelia polysaccharide (LMP) showed a reversible inhibition on α-glucosidase activity in a mixed-type manner. LMP inhibited AGEs formation effectively. In addition, LMP alleviated high glucose-induced oxidative stress and apoptosis in HUVECs by inhibiting the MAPK signaling pathways. Highlights: LMP showed a reversible inhibition on α-glucosidase activity in a mixed-type manner. LMP had remarkable capacity to inhibit the formation of AGEs in glucose-BSA model. LMP alleviated the oxidative stress induced by high glucose in HUVECs significantly. LMP is a potential agent for diabetes and related complications via multiple targets. Abstract: At present, diabetes and diabetic complications have become one of the serious diseases affecting human health. In this study, the inhibitory effects of Lentinus edodes mycelia polysaccharide (LMP) on α-glucosidase activity, the formation of advanced glycation end products (AGEs) and high glucose-induced human umbilical vein endothelial cells (HUVECs) damage were explored. The interaction between LMP and α-glucosidase and the inhibition against AGEs formation were investigated with spectroscopic techniques. The results revealed that LMP had a reversible inhibition on α-glucosidase activity in a mixed-type manner. When the concentration of LMP was 2.7 mM, the inhibition rate was 34.38 %. LMP quenched the fluorescence of α-glucosidase through the static quenching and formed the LMP-α-glucosidase complex. At 310 K, the number of binding sites ( n ) and binding constant ( Kb ) were 1.01 and 3.71 × 10 4 L mol −1, respectively. In addition, LMP could inhibit the formation of AGEs. Compared with 40 mM glucose treatment group, treatment with 0.05 mM LMP for 48 h increased the cell viability from 70.17% to 91.14% and decreased ROS production from 3.33-fold to 1.21-fold. LMP inhibited high glucose-induced activation of MAPK signaling pathways. These findings may promote the application of LMP in the functional food industry.